A correlation study between weather and atmosphere with COVID-19 pandemic in Islamabad, Pakistan - Aslam, Bilal; Khalil, Umer; Azam, Umar; Maqsoom, Ahsen (Spatial information research (Online), 2021)
The present research aims to investigate the association amid weather and the most recent pandemic of COVID-19 in Islamabad, the capital of Pakistan. The source of COVID-19 surveillance data for the secondary data analysis was the Pakistan’s Ministry of National Health Services Regulations and Coordination. The weather data obtained from the Pakistan Metrological Department (PMD) was exercised in this research. The components of weather include wind speed (m/s), precipitation level (mm), normal, mean, maximum, and minimum temperature (°C). For data analysis, a non-parametric correlation test was used due to the reason that normality was not satisfied. Precipitation level (r =  − 0.285; p =0 .022), normal temperature (r = 0.293; p = 0.019) as well as the maximum temperature (r = 0.347; p = 0.005) were very much associated with COVID-19 virus. Pollution data (showing the concentration of NO 2 ) of the specific region comprising the study area extracted from the Sentinel-5P satellite was also compared for the two years (2019 and 2020). Since the country will be entering to a new weather season, the conclusions may well assist the strategy and decision-makers in the deterrence of COVID-19.